Directive Speech Acts in The Short Film “Makr” by Hana Kazim (George Yule`s Pragmatic Study) - Febyanti Fadhliatul (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2023)
This research discusses directive speech acts in the short film Makr. A directive speech act is a type of speech act that is used by the speaker to order the hearer to do something. The aim of this research is to describe the forms and functions of directive speech acts in films. The method used is descriptive qualitative method. The data in this research are utterances showing directive speech acts in the short film Makr. The technique used in this research is the technique of observing, sorting, and recording with the pragmatic equivalent analysis method. The results of this research indicate that directive speech acts in the short film Makr take the form of direct literal speech acts, direct non-literal speech acts, literal indirect speech acts, and indirect non-literal speech acts. The functions of directive speech acts in the short film Makr are requestives, questions, requirements, prohibitives, permissives, and advisories. Keywords: Pragmatics; Speech Act; Directive; Short Film Makr